Successful Iohexol Sclerotherapy for Non-parasitic Chyluria: A Case Report - Shashikant Asabe; Onkar Sangha; Vikram Satav; Vilas Sabale (Journal of Clinical and Diagnostic Research)
Chyluria is a medical condition characterised by the passing of milky urine due to the abnormal drainage of lymphatic fluid, known as chyle, into the urinary tract. This condition can result from a variety of aetiologies, both parasitic and non-parasitic, with Wuchereria bancrofti being the primary causative agent. Diagnosis includes clinical presentation, laboratory investigations, and imaging studies. Management encompasses a wide array of conservative therapies and surgical interventions. A 60-year-old male presented with chyluria and chyle clots for one year. He had received medical treatment for filariasis and dietary modifications at various hospitals before being referred to this centre. The patient was investigated and diagnosed with non-parasitic chyluria due to a left pyelo-lymphatic fistula and subsequently underwent sclerotherapy with Iohexol contrast, which resulted in complete resolution. This minimally invasive procedure involves the injection of a contrast agent that helps seal affected lymphatic vessels, preventing further chyle leakage into the urinary system. Severe chyluria can be effectively managed with Iohexol contrast sclerotherapy. This case underscores the importance of timely intervention and the use of sclerotherapy with Iohexol contrast as a treatment for severe chyluria, offering a promising therapeutic option for patients with persistent or complicated cases.